Axial Compressive Behavior of Steel Fiber-Reinforced Recycled Coarse Aggregate Concrete-Filled Short Circular Steel Columns - Qiao-Huan Wang; Jiong-Feng Liang; Chun-Feng He; Wei Li (Advances in Materials Science and Engineering)
This paper attempts to explore the effects of recycled coarse aggregate content, steel fiber content, and concrete strength on the axial compressive behavior of steel fiber-reinforced recycled coarse aggregate (RCA) concrete-filled circular steel stub columns. A total of 14 short columns are tested. The results show that using RCA in concrete will reduce the bearing capacity of short columns, but the increase in steel fiber content and concrete strength can eliminate this shortcoming. Not only that, the concrete strength has a great influence on the ductility and stiffness of the specimen.